Mini-sternotomy versuMini-sternotomy versuss conventional sternotomy in aortic valve replacement surgery; A comparative study - Mohamed KhalidBakr Ali; Mohamed Moustafa Abdelaal; Wael Mohamed Elfeky; Amr Ahmed Abdou Ettish (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess safety; efficacy and efficiency of mini-sternotomy in aortic valve replacement in comparison to conventional sternotomy on short term follow up. Methods: This comparative study between 45 patients having aortic valve replacement via full sternotomy versus 45 others planned for upper j-shaped mini-sternotomy, was conducted from May 2019 to February 2022 in Kafrelsheikh university hospital, Egypt. Data was collected and statistically analysed to assess outcomes. Results: Mini-Sternotomy approach was compared to conventional approach on the aspects of cardio pulmonary bypass (CPB) (p=0.153) and cross clamp (CC) time (p=0.673),. There was significantly less postoperative bleeding (p<0.001), rate of blood transfusion (p<0.001), duration of ICU stay (p=0.013) and total hospital stay (p=0.022) in ministernotomy approach in comparison to conventional sternotomy. Conclusion: For primary isolated AVR, less invasive techniques are a realistic, practical, and good alternative that offers better postoperative results than Full Sternotomy. Keywords: Aortic valve, sternotomy, Blood Transfusion, Pain, Intensive Care Units